Analisis Pengaruh Tekstur Dan C-Organik Tanah Terhadap Produksi Tanaman Ubi Kayu (Manihot esculenta Crantz) Di Kecamatan Pegajahan Kabupaten Serdang Bedagai - Jayagust K.A Junior Sinaga,; Supriadi Supriadi; Alida Lubis (Universitas Sumatera Utara, 2014)
The Analysis of Soil Texture and C-Organic Influence for Cassava Production(Manihot esculenta Crantz.) at Sub District Pegajahan, Serdang regency. The research purpose is todetermine the effect of soil texture and C-organic influence of cassava production at Sub DistricPegajahan. The research was conducted on June-July 2013. Sample was taken have a lot of 50farmers by using simple random sampling methode. The parameters was being analiysed were soiltexture and C-organic. Then appraisal data processed with regression method. Final research resultsshown that C-organic effect toward cassava production, sand, silt and clay has no significant effecttoward cassava production. The optimal C-organic for cassava production is 0,203 %, while themean C-organic more than from the optimal C-organic at Sub Distric Pegajahan.Keywords : Soil Texture, C-Organic, Cassava Production